Degree of Representation of Jordan University Students on the Concepts of National Identity: from their Point of View - Abu Salah, Faten Mahmoud (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the degree to which the students of the University of Jordan represent concepts of national identity from their point of view. To achieve the goal of the study, the researchers used the descriptive approach. The tool was represented in a questionnaire consisting of (20) paragraphs. After confirming its stability and sincerity, it was applied to a random sample consisting of (400) A student and a student from the University of Jordan, the results showed that the total degree was obtained to represent the students of the University of Jordan for the concepts of national identity from their point of view on an arithmetic average (3.75) with a high degree. In addition to, there are statistically significant differences appeared in a degree that represents the students of the University of Jordan for the concepts of national identity attributed to variable gender, while there are no statistically significant differences appeared in a degree that represents the students of the University of Jordan for the concepts of national identity attributed to variable (college and year). In light of these results, a number of proposals and recommendations were presented, the most important of which was interest in creating a generation that adheres to its national identity, consolidating elements of national heritage from childhood, emphasizing the importance of the Arabic language as the language of the Qur’an, and informing them of the honorable Arab history to be proud of their past belonging to their present.
Keywords: National Identity; University of Jordan students